Fenómenos naturales y su interpretación en la etapa prehispánica - Zegarra Moretti, Carlos Benjamín (Mercurio Peruano, 2020)
The effects of natural phenomena, in particular “El Niño” Phenomenon, affected the cosmology of the pre-Hispanic cultures. Archaelogical investigations and historial sources (like the Huarochiri manuscript) reveal changes in the cultures of Vicus, Lambayeque, Moche, Chimu and the Incas that were caused by flooding. These effects survived through structural changes in the construction of these pre-Hispanic societies, as well as the creation of linguistic terms, myths and iconography, especially in Andean religion.